Composition Of Termites In Three Different Soil Types Across Oil Palm Agroecosystem Regions In Riau (Indonesia) And Johor (Peninsular Malaysia) - Saputra, A; Nasir, DM; Jalaludin, NA; Halim, M; Bakri, A; Esa, MFM; Hazmi, IR; Faszly Rahim (Malaysian Palm Oil Board, 2024)
Indexed by WOS/SCOPUS